On the Notion of Text and Its Boundaries in the Context of Semiotics and Communication - Gilyazova, Olga Sergeevna (Journal of History Culture and Art Research, 2020)
The article presents a terminological analysis of the notion of text in the context of semiotic and communication paradigms to define its boundaries and to disengage it from non-textual semiosis. The objectives were achieved through the application of general scientific methods (analysis, synthesis, description), the semioanalysis following Yu. M. Lotman’s methods and also structuralist and, to a certain degree, post-structuralist approaches. While performing the analysis, the author comes to the conclusion that the concept of infinite textualization of the actual reality, which is promoted by a number of post-structuralists, tends to neglect both the complex dialectical relationship and the opposition between the text and actual reality. The article defines the ontological status of a text as a specific conditional reality. Then, differences and similarities between the text, other conditional realities, and the actual reality can be more clearly identified, which is quite important, considering the current post-modernist tendency to blend the text and extra-textual realities. The conclusion is that the main characteristics of the text are ontological conditionality, semiotic property, informativity, communicative nature and origin, the presence of an intentional sender, artificial origin, accessibility for universal perception, coherence, integrity, and completeness. To sum up, I define the text as a semiotic conditional reality generated by a communicative situation with non-degenerated planes of expression and content, and characterized by the unity of syntagmatic cohesion and paradigmatic integrity, certain systematicity, and completeness.